2016
DOI: 10.18178/ijesd.2016.7.8.844
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation of Landfill Methane and Carbon Dioxide Emissions in a Tropical Climate

Abstract: Abstract-Landfill gas (LFG) emissions were measured in a landfill in tropical conditions in Malaysia to investigate seasonal variations in methane (CH 4 ) and carbon dioxide (CO 2 ) emissions. The study results showed that CH 4 and CO 2 emissions were ranged from 0 to 1,602 g m -2 d -1 and 5 to 2,753 g m -2 d -1 during wet and dry seasons, respectively, and higher CH 4 and CO 2 emissions were found during the wet season than in the dry season. It is concluded that special consideration must be given to landfil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 14 publications
2
20
1
Order By: Relevance
“…Previous studies have diagnosed some seasonality for CH 4 emissions (Lowry et al, 2001;McKain et al, 2015). As examples of the potential explanations for this phenomenon, the seasonality of the gas consumption for heating (with large consumption for lower temperatures, especially in winter) could drive seasonal variations in the gas leakage (Jeong et al, 2012), and the seasonal variations in the meteorology (pressure, humidity, temperature) could impact the decomposition and release of CH 4 , and thus the emissions, from the waste storage and waste treatment sector (Börjesson and Svensson, 1997;Masuda et al, 2015;Abushammala et al, 2016). However, characterising such seasonal variations is a difficult task, which may vary substantially depending on the sectors and cities.…”
Section: Simulation Of the Atmospheric Transport Of Comentioning
confidence: 99%
“…Previous studies have diagnosed some seasonality for CH 4 emissions (Lowry et al, 2001;McKain et al, 2015). As examples of the potential explanations for this phenomenon, the seasonality of the gas consumption for heating (with large consumption for lower temperatures, especially in winter) could drive seasonal variations in the gas leakage (Jeong et al, 2012), and the seasonal variations in the meteorology (pressure, humidity, temperature) could impact the decomposition and release of CH 4 , and thus the emissions, from the waste storage and waste treatment sector (Börjesson and Svensson, 1997;Masuda et al, 2015;Abushammala et al, 2016). However, characterising such seasonal variations is a difficult task, which may vary substantially depending on the sectors and cities.…”
Section: Simulation Of the Atmospheric Transport Of Comentioning
confidence: 99%
“…Some studies have shown that higher CH 4 and CO 2 emissions are more common during the wet season than the dry season. According to Abushammala, Basri and Younes (2016), landfill gas emissions were measured in a landfill under tropical conditions in Malaysia to investigate seasonal variations in CH 4 and CO 2 emissions. The study results revealed that CH 4 and CO 2 emissions varied from 0 to 1,602 g m -2 d -1 and from 5 to 2,753 g m -2 d -1 during the wet and dry seasons, respectively, corroborating that higher CH 4 and CO 2 emissions are more frequent during the wet season than the dry season.…”
Section: Resultsmentioning
confidence: 99%
“…The MSW dumped at Pirana has been broadly classified as organic matters (72%), earth material (13.5%), plastic (6.8%), paper (5.7%), and metal/glass (2%) ( Singh et al, 2008 ). Among a mixture of gases, the burning and decomposition of landfill organic materials leads to the release mainly of CH 4 (45–60%) and CO 2 (40–55%) (e.g., Abushammala et al., 2016 ). Also, trace amounts of various VOCs are emitted from the decomposition and burning of organic materials.…”
Section: Methodsmentioning
confidence: 99%